3D analysis of the myenteric plexus of the human bowel by X-ray phase-contrast tomography – a future method?. (2nd October 2020) - Peruzzi, Niccolò; Veress, Béla; Dahlin, Lars B.; Salditt, Tim; Andersson, Mariam; Eckermann, Marina; Frohn, Jasper; Robisch, Anna-Lena; Bech, Martin; Ohlsson, Bodil
Abstract: Objectives: Light microscopical analysis in two dimensions, combined with immunohistochemistry, is presently the gold standard to describe the enteric nervous system (ENS). Our aim was to assess the usefulness of three-dimensional (3D) imaging by X-ray phase-contrast tomography in evaluating the ENS of the human bowel. Material and methods: Myenteric ganglia were identified in full-thickness biopsies of the ileum and colon by hematoxylin & eosin staining. A1-mm biopsy punch was taken from the paraffin blocks and placed into a Kapton ® tube for subsequent tomographic investigation. The samples were scanned, without further preparation, using phase-contrast tomography at two different scales: overview scans (performed with laboratory setups), which allowed localization of the nervous tissue (∼1µm effective voxel size); and high-resolution scans (performed with a synchrotron endstation), which imaged localized regions of 320x320x320 µm 3 (176 nm effective voxel size). Results: The contrast allowed us to follow the shape and the size changes of the ganglia, as well as to study their cellular components together with the cells and cellular projections of the periganglional space. Furthermore, it was possible to show the 3D network of the myenteric plexus and to quantify its volume within the samples. Conclusions: Phase-contrast X-ray tomography can be applied for volume analyses of the human ENS and to study tissue components in unstained paraffin-embedded tissue biopsies. This technique could potentially be used to study disease mechanisms, and to compare healthy and diseased tissues in clinical research.